2012
DOI: 10.1104/pp.112.209791
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Putative Osmosensor Arabidopsis Histidine Kinase1 in Dehydration Avoidance and Low-Water-Potential Response    

Abstract: The molecular basis of plant osmosensing remains unknown. Arabidopsis (Arabidopsis thaliana) Histidine Kinase1 (AHK1) can complement the osmosensitivity of yeast (Saccharomyces cerevisiae) osmosensor mutants lacking Synthetic Lethal of N-end rule1 and SH3-containing Osmosensor and has been proposed to act as a plant osmosensor. We found that ahk1 mutants in either the Arabidopsis Nossen-0 or Columbia-0 background had increased stomatal density and stomatal index consistent with greater transpirational water lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 61 publications
(107 reference statements)
1
70
0
1
Order By: Relevance
“…Declining cell volume may trigger signals via sensors within the cytoskeleton, or the cell membrane (i.e. sensors of membrane tension, of membrane protein distances, of the increase of specific ions or metabolites), or at the interface of cell membrane and cell wall (Christmann et al, 2013;Kumar et al, 2013;Haswell and Verslues, 2015;Pandey, 2017). These proteins may directly sense negative effects on processes or structures threatened by cell volume shrinkage, such as the cytoskeleton, membrane-cell wall contacts, or ion transport, even before detrimental biochemical effects arise (Oliver, 1996;Zhang et al, 2001;Pandey 2017).…”
Section: Speciesmentioning
confidence: 99%
“…Declining cell volume may trigger signals via sensors within the cytoskeleton, or the cell membrane (i.e. sensors of membrane tension, of membrane protein distances, of the increase of specific ions or metabolites), or at the interface of cell membrane and cell wall (Christmann et al, 2013;Kumar et al, 2013;Haswell and Verslues, 2015;Pandey, 2017). These proteins may directly sense negative effects on processes or structures threatened by cell volume shrinkage, such as the cytoskeleton, membrane-cell wall contacts, or ion transport, even before detrimental biochemical effects arise (Oliver, 1996;Zhang et al, 2001;Pandey 2017).…”
Section: Speciesmentioning
confidence: 99%
“…In Arabidopsis, the cytokinin receptor histidine kinases AHK2, AHK3, and CRE1 have been shown to play important roles in the regulation of plant abiotic responses in both ABA-dependent and ABA-independent signalling pathways (Tran et al 2007); on the other hand, the homologous gene AHK1 was identified as an osmotic stress sensor that positively regulates abiotic stress (Wohlbach et al 2008;Kumar et al 2013;Tran et al 2007). Increasing evidence suggests a negative role for cytokinin signalling in cold-and ABA-mediated abiotic stress.…”
Section: Cytokinin and Cold Stressmentioning
confidence: 98%
“…The osmotic stress response is initiated by two yeast transmembrane osmosensors that act upstream of a mitogen-activated protein kinase (MAPK) signaling cascade to control gene expression in the Hog1 (for high-osmolality glycerol response1) signaling pathway (Hohmann, 2002). There is evidence to suggest that a similar pathway may be present in plants (Urao et al, 1999;Tran et al, 2007;Wohlbach et al, 2008;Kumar et al, 2013), and MAPK phosphorylation likely plays an important role in the osmotic stress response, as MAPK cascades are known to regulate several abiotic and biotic stress response pathways (Rodriguez et al, 2010).…”
mentioning
confidence: 99%